2014
DOI: 10.1002/2013wr014506
|View full text |Cite
|
Sign up to set email alerts
|

The importance of observed gradients of air temperature and precipitation for modeling runoff from a glacierized watershed in the Nepalese Himalayas

Abstract: The performance of glaciohydrological models which simulate catchment response to climate variability depends to a large degree on the data used to force the models. The forcing data become increasingly important in high-elevation, glacierized catchments where the interplay between extreme topography, climate, and the cryosphere is complex. It is challenging to generate a reliable forcing data set that captures this spatial heterogeneity. In this paper, we analyze the results of a 1 year field campaign focusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
308
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 241 publications
(347 citation statements)
references
References 39 publications
37
308
2
Order By: Relevance
“…In addition, exposed debris alters near-surface meteorological fields and their elevational gradients, which are often key modeling parameters used to extrapolate forcing data from a point location (e.g., an automatic weather station) over the rest of the glacier surface (e.g., Marshall et al, 2007;Gardner et al, 2009;Reid et al, 2012). The lapse rate in air temperature at lower elevations is more than one degree steeper in DEB, as a result of surface temperatures exceeding the melting point and a higher net turbulent transfer of sensible heat to the atmosphere that produces higher near-surface air temperatures, and is higher than values reported for smaller debris-covered glaciers (Reid et al, 2012) and in the eastern Himalaya, where the monsoon circulation is more dominant (Immerzeel et al, 2014b). eling approach on the Baltoro glacier, and with the measured rates reported by Mayer et al (2010).…”
Section: Discussionmentioning
confidence: 82%
“…In addition, exposed debris alters near-surface meteorological fields and their elevational gradients, which are often key modeling parameters used to extrapolate forcing data from a point location (e.g., an automatic weather station) over the rest of the glacier surface (e.g., Marshall et al, 2007;Gardner et al, 2009;Reid et al, 2012). The lapse rate in air temperature at lower elevations is more than one degree steeper in DEB, as a result of surface temperatures exceeding the melting point and a higher net turbulent transfer of sensible heat to the atmosphere that produces higher near-surface air temperatures, and is higher than values reported for smaller debris-covered glaciers (Reid et al, 2012) and in the eastern Himalaya, where the monsoon circulation is more dominant (Immerzeel et al, 2014b). eling approach on the Baltoro glacier, and with the measured rates reported by Mayer et al (2010).…”
Section: Discussionmentioning
confidence: 82%
“…Higher inter-annual variability of nival-glacier regime SELR as 20 observed for Beas and Sutlej basins indicate more complex processes driving these changes and raise questions regarding its use for modeling snow and glacier melt, especially for modeling future runoff and glacier fluctuations. Various researchers have shown that the glacier and snowmelt estimation by degree day method is highly sensitive to the near surface lapse rate Marshall et al, 2007 andImmerzeel et al, 2014). This result points towards the need for revisiting the benchmark glacier monitoring strategy (Fountain et al, 1997) for mountain glaciers.…”
Section: Discussionmentioning
confidence: 99%
“…Collected data are distributed on each grid by using temperature, and precipitation gradients. In this study the precipitation gradient is used as described by (Immerzeel et al, 2014) and the temperature gradient is calculated from station data available from Yala and Kyangjing temperature data.…”
Section: Hydro-meteorological Datamentioning
confidence: 99%